G-quadruplexes and associated proteins in aging and Alzheimer’s disease - Vijay Kumar, M. J.; Morales, Rodrigo; Tsvetkov, Andrey S. (Frontiers in Aging, 2023)
Aging is a prominent risk factor for many neurodegenerative disorders, including Alzheimer’s disease (AD). AD is characterized by progressive cognitive decline, memory loss, and neuropsychiatric and behavioral symptoms, accounting for most of the reported dementia cases. This disease is now becoming a major challenge and burden on modern society, especially with the aging population. Over the last few decades, a significant understanding of the pathophysiology of AD has been gained by studying amyloid deposition, hyperphosphorylated tau, synaptic dysfunction, oxidative stress, calcium dysregulation, and neuroinflammation. This review focuses on the role of non-canonical secondary structures of DNA/RNA G-quadruplexes (G4s, G4-DNA, G4-RNA), G4-binding proteins, and helicases, and their roles in aging and AD. Being critically important for cellular function, G4s are involved in the regulation of DNA and RNA processes, including replication, transcription, translation, RNA localization, and degradation. Recent studies also highlighted G4-DNA’s roles in inducing DNA double-stranded breaks that cause genomic instability and G4-RNA’s participation in regulating stress granule formation. This review emphasizes the significance of G4s in aging processes and how their homeostatic imbalance may contribute to the pathophysiology of AD.